A self-powered organolead halide perovskite single crystal photodetector driven by a DVD-based triboelectric nanogenerator. Issue 3 (20th November 2015) - Fang, Huajing; Li, Qiang; Ding, Jie; Li, Nan; Tian, He; Zhang, Lijing; Ren, Tianling; Dai, Jiyan; Wang, Liduo; Yan, Qingfen
Abstract : The integration of a CH3 NH3 PbI3 single crystal photodetector with a TENG leads to a self-powered photodetector with a large responsivity and a wide detection range. Abstract : Organolead halide perovskites have attracted extensive attention as light harvesting materials for optoelectronic devices due to their high charge carrier mobility, high photoconversion efficiency, and long charge diffusion length. In this study, we present the first self-powered organolead halide perovskite single crystal photodetector driven by a triboelectric nanogenerator (TENG). A high-performance planar photodetector showing a responsivity of 7.92 A W −1 to white light under a bias of 4 V was fabricated on the (100) facet of a bulk CH3 NH3 PbI3 perovskite single crystal. Furthermore, we demonstrate a cost-effective approach to the fabrication of a drum-shaped TENG by using two used digital versatile discs (DVDs), which could generate a high output of up to 200 V and 55 μA. By integrating the CH3 NH3 PbI3 single crystal photodetector with the TENG, the self-powered device exhibited a large responsivity of 196 V (mW cm −2 ) −1 and a wide detection range from 10 μW cm −2 to 100 mW cm −2 . These results provide a new strategy for driving the organolead halide perovskite photodetector with the energy harvested from the environment rather than an external power supply.